Health-related quality of life in patients with high-risk low-grade glioma (EORTC 22033-26033): a randomised, open-label, phase 3 intergroup study - Reijneveld, Jaap C.; Wick, Antje (The lancet. Oncology, 2016)
Background - Temozolomide chemotherapy versus radiotherapy in patients with a high-risk low-grade glioma has been shown to have no significant effect on progression-free survival. If these treatments have a different effect on health-related quality of life (HRQOL), it might affect the choice of therapy. We postulated that temozolomide compromises HRQOL and global cognitive functioning to a lesser extent than does radiotherapy. - Methods - We did a prospective, phase 3, randomised controlled trial at 78 medical centres and large hospitals in 19 countries. We enrolled adult patients (aged ≥18 years) with histologically confirmed diffuse (WHO grade II) astrocytoma, oligodendroglioma, or mixed oligoastrocytoma, with a WHO performance status of 2 or lower, without previous chemotherapy or radiotherapy, who needed active treatment other than surgery. We randomly assigned eligible patients (1:1) using a minimisation technique, stratified by WHO performance status (0-1 vs 2), age (<40 years vs ≥40 years), presence of contrast enhancement on MRI, chromosome 1p status (deleted vs non-deleted vs indeterminate), and the treating medical centre, to receive either radiotherapy (50·4 Gy in 28 fractions of 1·8 Gy for 5 days per week up to 6·5 weeks) or temozolomide chemotherapy (75 mg/m2 daily, for 21 of 28 days [one cycle] for 12 cycles). The primary endpoint was progression-free survival (results published separately); here, we report the results for two key secondary endpoints: HRQOL (assessed using the European Organisation for Research and Treatment of Cancer’s [EORTC] QLQ-C30 [version 3] and the EORTC Brain Cancer Module [QLQ-BN20]) and global cognitive functioning (assessed using the Mini-Mental State Examination [MMSE]). We did analyses on the intention-to-treat population. This study is closed and is registered at EudraCT, number 2004-002714-11, and at ClinicalTrials.gov, number NCT00182819. - Findings - Between Dec 6, 2005, and Dec 21, 2012, we randomly assigned 477 eligible patients to either radiotherapy (n=240) or temozolomide chemotherapy (n=237). The difference in HRQOL between the two treatment groups was not significant during the 36 months’ follow-up (mean between group difference [averaged over all timepoints] 0·06, 95% CI −4·64 to 4·75, p=0·98). At baseline, 32 (13%) of 239 patients who received radiotherapy and 32 (14%) of 236 patients who received temozolomide chemotherapy had impaired cognitive function, according to the MMSE scores. After randomisation, five (8%) of 63 patients who received radiotherapy and three (6%) of 54 patients who received temozolomide chemotherapy and who could be followed up for 36 months had impaired cognitive function, according to the MMSE scores. No significant difference was recorded between the groups for the change in MMSE scores during the 36 months of follow-up. - Interpretation - The effect of temozolomide chemotherapy or radiotherapy on HRQOL or global cognitive functioning did not differ in patients with low-grade glioma. These results do not support the choice of temozolomide alone over radiotherapy alone in patients with high-risk low-grade glioma. - Funding - Merck Sharp & Dohme-Merck & Co, National Cancer Institute, Swiss Cancer League, National Institute for Health Research, Cancer Research UK, Canadian Cancer Society Research Institute, National Health and Medical Research Council, European Organisation for Research and Treatment of Cancer Cancer Research Fund.
Gesehen am 21.10.2021